A new fluorimetric method for simultaneous determination of lipid and protein hydroperoxides in muscle foods with the use of diphenyl-1-pyrenylphosphine (DPPP). (June 2020) - Cropotova, Janna; Rustad, Turid
Abstract: A new fluorimetric assay for simultaneous determination of lipid and protein hydroperoxides in muscle foods by the use of diphenyl-1-pyrenylphosphine (DPPP) was proposed in the study. Non-fluorescent DPPP that reacts with hydroperoxides stoichiometrically to yield fluorescent DPPP oxide, was used as a fluorescent dye to determine lipid and protein peroxidation in fish samples during frozen storage. The novel sensitive DPPP-assay developed for analysis under fluorescence microscopy conditions was based on this reaction. A good linear correlation between the amount of lipid hydroperoxides measured by the developed DPPP-assay and the peroxide value measured by iodometric titration was observed. Also, increase in fluorescence intensity from the reaction of DPPP with protein hydroperoxides in fish samples showed linear relation to the amount of cumene hydroxide added over a wide concentration range. The method was successfully applied on fish samples and can be used for fast assessment of primary oxidation stress in muscle foods. Highlights: The DPPP method is precise and correlated well with the iodometric titration assay. Fluorescence microscopy allowed quantification of both lipid and protein peroxides. Fluorescence microscopy visualized both lipid and protein peroxides. The iodometric titration and fluorescence microscopy assays were compared.